Jacob's tears : the priestly work of reconciliation - Douglas, Mary, 1921-2007 (Oxford University Press, 2006)
Who is Israel? Who were the priestly authors of the Pentateuch? This anthropological reading of the Bible starts by asking why the Book of Numbers lists the 12 tribes of Israel seven times.